A Systematic Review of the Potential Effects of Propolis Extracts on Experimentally-induced Diabetes - Cunha, Gustavo Aparecido Da (2023)
Oxidative stress (OS) is involved in the development of diabetes mellitus (DM) and its complications. Thus, OS reduction may be an important strategy for DM therapy. Propolis is bee resins with high antioxidant activity and is used in the treatment of different diseases, including DM. Therefore, in this systematic review, we evaluated the impact of propolis administration in diabetic animals. We used the PRISMA strategy to collect preclinical studies published in English up to November 2021 in three databases (PubMed/Medline, Scopus, and Web of Science). We used the SYRCLE tool to analyze the risk of methodological bias. Our primary search returned 198 studies, of which 14 were considered eligible to be included in this review. The administration of propolis induced a hypoglycemic effect in the treated animals, which is probably due to the reduction of OS. The animals showed restoration of endogenous antioxidant defenses and reduced levels of markers for OS. The administration of propolis resulted in improvement in the lipid profile of treated animals. Our risk of bias assessment showed a methodological quality score of less than 30% due to a lack of randomization, blinding, and proper allocation of animals. Heterogeneity in treatments, lack of results, and use of non-standard extracts are limitations in our data analysis. Despite these limitations, propolis induced a significant hypoglycemic effect in diabetic animals when compared to untreated controls. This effect was associated with a reduction in OS, a process mediated by ROS neutralization and restoration of endogenous antioxidant defenses.